Evolutionary computation with intelligent systems : a multidisciplinary approach to society 5.0 - Chauhan, R. S. (Ranjit Singh) (Boca Raton : CRC Press, 2022)
"This book focuses on cutting-edge innovations and core theories, principles, and algorithms applicable to a wide area. Real-life applications, case studies, and examples are included along with emerging trends, design, and optimized solutions pivoting around the needs of Society 5.0. Evolutionary Computation with Intelligent Systems: A Multidisciplinary Approach to Society 5.0 provides a holistic view of Evolutionary Computation techniques with principles, procedures, and future applications with real-life examples. The book comprehensively explains Evolutionary Computation, design, principles, development trends, and optimization and describes how it can transform the operating context of the organization. It exemplifies the potential of Evolutionary Computation for the next generation and the role of cloud computing in shaping Society 5.0. It also provides insight into various platforms, paradigms, techniques, and tools used in diverse fields. This book appeals to all kinds of readers such as academicians, researchers, research scholars, and postgraduates"--
SECTION A: Principles, Types, Theories, and Applications of Evolutionary Computation. 1. Evolutionary Computation for Optimized Solutions Towards Society 5.0. 2. Exploiting Machine Learning for Evolutionary Training of Machines. 3. Image Processing for Knowledge Management and Effective Information Extraction Through Optimization. 4. Evolutionary Computation Framework for Handling Resource Constraint Mobile Environments. SECTION B: Evolutionary Computation: Emerging Trends and Implications. 5. Smart Systems for Global Sustainability with Enhanced Computing. 6. Recommender System: Techniques for Optimized Decision Making. 7. Innovations in Healthcare Using Smart Systems Equipped with Evolutionary Computation. 8. Exploiting Evolutionary Computation Techniques for Service Industries. SECTION C: Next Generation Evolutionary Computation Techniques and Innovations. 9. Performance Analysis of Industrial Unit Using Evolutionary Computation Methods. 10. Reliability and Availability System Modeling with Evolutionary Computation Techniques. 11. Maintainability of System Through Evolutionary Computation Techniques. 12. Simulation and Analysis of Quadratic Assignment Problems Using Evolutionary. Computation. SECTION D: Evolutionary Computation for Society and Business Organizations. 13. Evolutionary Computation for Total Quality Management. 14. Consumer Behavior and Satisfaction Through Evolutionary Computation. 15. Decision Support System and Marketing Using Evolutionary Computation Techniques. 16. Performance Modeling and Optimization for the Stock Preparation with Evolutionary Computation.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Industrial applications; Society 5.0.; Evolutionary programming (Computer science); Internet of things; TECHNOLOGY / Operations Research